Sefarad, Revista del Intituto Arias Montano de Estuios Hebraicos y Oriente Próximo, C.S.I.C., Madrid-Barcelona: tomo 7 (1947), tomo 8 (1948). - Lope Blanch, Juan M. (El Colegio de México, 1955)
Se reseñó: Sefarad: tomo 7 (1947), tomo 8 (1948).